INTERACTION BETWEEN DENTO-MAXILLOFACIAL ANOMALIES AND GENERAL-SOMATIC HUMAN CONDITION (LITERATURE REVIEW) - L.V. Smaglyuk; H.V. Voronkova; A.Ye. Karasiunok; A.V. Liakhovska; V.I. Smaglyuk (Український стоматологічний альманах)
The main task of modern orthodontics is to create a balanced and morphologically stable occlusion in harmony with facial aesthetics and functional adaptation. Over the last decade, there has been a clear trend towards an increase in the prevalence of malocclusion, which reaches 80% according to current scientific literature and sometimes it exceeds this percentage. Researchers note a constant and statistically significant correlation between the permanent occlusion pathology and the state of somatic health in adolescence. On the other hand, the interdisciplinary approach is one of the most urgent tasks of modern orthodontics and a constant object of searching for new methods of diagnosis and treatment.